Australian attitudes towards innovation, work and technology: Towards a cultural explanation. (1st March 2021) - Charles, Michael B.; Ryan, Neal; Tuffley, David; Noble, David; Stonecash, Robin
Abstract : Australia, despite its G20 status, has not been performing as well in innovation in high-technology sectors as its educational levels and sustained growth would suggest. Australia has found it difficult to emerge from an economy based on resources and agriculture to a services economy based on knowledge and the application of technology. Several reasons have been put forward over the years. This study considers one reason that has not been considered in any detail – culture and national identity. In this paper, we look closely at a number of artefacts of popular culture from the late 1800s to the present day (such as art, poetry, song and film). These continue to underpin Australia's national identity, despite the multicultural and multiethnic nature of modern Australia. This study argues that the current Australian attitude to work, technology and innovation is strongly rooted in the egalitarian and anti-authoritarian ethos associated with what has been termed the 'Australian legend' or the 'pioneer legend'. A national discourse with emphasis on hyper-masculine hard work as opposed to education and innovation has favoured policies to assist the resource and agricultural sectors of the economy, rather than sectors capable of creating greater value.